FAMILY EMPOWERMENT PASIEN SCHIZOPHRENIA - Julahir Hodmatua; Saiful Barubara; Lenni Afriani Batubara (Jurnal Penelitian Kesmasy, 2023)
Schizophrenia is a chronic mental disorder, requiring longer and continuous treatment continuously in any circumstances that may fluctuate. The success of treatment in the hospital can be in vain if it is not continued at home because it can cause recurrence and cause risk to family. The ability to take care for the family member can be trained with family empowerment through efforts for increasing awareness and ability to take care for their family member. The objective of this systematic review is tosummarize the description of the empowerment of family of patient with schizophrenia.The method used is the prism method . A systematic review was conducted by searching for literature related to the chosen theme, such as “Family Empowerment: Family Psychoeducation, Family Caregivers, Family Caring, Family-center and patients with schizophrenia. Literature search through clinical key, Proqueste, research gate, Oamjms.eu and google scholar. The literature search was taken based on journals articles from 2019 to 2022. A total of 11 studies were included in this review. The results of the study mostly raised the theme of family empowerment, namely using educational or psychoeducational models, family strength, care givers and family caring. The research method used is quantitative method with various designs such as Quasi-experimental: 7 studies, qualitative: 2 studies and systematic review: 2 studies. Most of the study results show that the intervention of empowering the families of schizophrenic patients has succeeded in increasing the knowledge of the patient's family regarding the condition of the disease, treatment and various other aspects, especially those related to the patient's relapse. Family empowerment shows a direct impact on increasing family knowledge, resilience and coping abilities related to the care of patients with schizophrenia or other mental disorders.